2018
DOI: 10.1371/journal.pone.0199609
|View full text |Cite
|
Sign up to set email alerts
|

Instances of erroneous DNA barcoding of metazoan invertebrates: Are universal cox1 gene primers too “universal”?

Abstract: The cytochrome c oxidase subunit I (cox1) gene is the main mitochondrial molecular marker playing a pivotal role in phylogenetic research and is a crucial barcode sequence. Folmer’s “universal” primers designed to amplify this gene in metazoan invertebrates allowed quick and easy barcode and phylogenetic analysis. On the other hand, the increase in the number of studies on barcoding leads to more frequent publishing of incorrect sequences, due to amplification of non-target taxa, and insufficient analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 68 publications
1
46
0
Order By: Relevance
“…Regarding other public databases (e.g. GenBank), effort is required to identify sequences with incorrect taxonomic assignment to avoid their use as reference data (Mioduchowska et al., ). (b) Development and validation of detailed and standardizable methods for fieldwork and extraction of the target specimens from their habitat matrix (water, soil, sediment, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding other public databases (e.g. GenBank), effort is required to identify sequences with incorrect taxonomic assignment to avoid their use as reference data (Mioduchowska et al., ). (b) Development and validation of detailed and standardizable methods for fieldwork and extraction of the target specimens from their habitat matrix (water, soil, sediment, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Hausmann et al., ), stronger linkage is forged between traditional taxonomic systems and reference sequences. Barcode campaigns that employ rigorous taxonomic identification of voucher specimens also provide a necessary step forward to identify database sequences that have been incorrectly assigned taxonomically, as it has been shown to occur in the genbank database (Mioduchowska, Jan, Gołdyn, Kur, & Sell, ).…”
Section: Large Coi‐bcr Reference Databases Provide a Powerful Link Tomentioning
confidence: 99%
“…However, examination of the loan records at the USNM revealed that the loan of material to Meiklejohn et al contained multiple specimens which were not included in their analyses or mentioned in their article-and among them, two were Strepsiptera (USNM ENT 01248370 and 01248357). Cross-contamination is a well-recognized risk when working with museum specimens so it is standard practice to check for its occurrence [13,14]. While Meiklejohn et al [10] exercised some precautions in their laboratory protocols such as the incorporation of negative controls in PCR, there was no evidence that they considered the possibility that some of their DNA sequences derived from non-target taxa.…”
Section: Factors Responsible For Four 'Errors' In Generic Assignmentmentioning
confidence: 99%
“…Yet, being a public database, it is inevitable that BOLD, as any other similar curation tool, might accrue erroneous data, sometimes signi cantly [2,6]. Taxonomic misidenti cations and/or taxonomic conundrums, cryptic species complexes, delimiting cryptic species, technical faults, such as de cient DNA extraction, PCR-based errors and foreign DNA contaminations, including bacterial sequences, especially COI sequences, are just some of the causes that may unavoidably generate erroneous data and inaccurate sequences [2,[6][7][8][9][10]. The above di culties may affect dramatically the accuracy of barcoding.…”
Section: Introductionmentioning
confidence: 99%